Karakteristik pH Kultur Kombucha Teh Hitam dengan Jenis Gula Berbeda pada Fermentasi Batch-Culture - Anggita Rahmi Hafsari; Ghanez Asriana A; Wilda Nur Farida; Mohammad Agus S (Gunung Djati Conference Series, 2021)
Kombucha is a fermented tea that utilizes the symbiotic relationship between bacteria and yeast that produces acid. The kombucha fermentation process will produce acid that continues to accumulate causes in changes in the pH value. One of the essential acids produced in this fermentation process is acetic acid. Acetic acid is produced by the bacteria in kombucha through ethanol oxidation. Ethanol is obtained from the sugar breakdown process carried out by yeast in kombucha. This study aims to determine the pH value of kombucha during the 15-day fermentation period in kombucha that was given different sugar additions. This research was conducted by observing kombucha and testing the pH every 3 days for 15 days. The results showed that the pH value of kombucha for 15 days changed values, namely H0(3.47), H3(3.43), H6(3.37), H9(3.24), H12(3.09), and H15 (3.08). The decrease in pH is caused by microbial activity in kombucha which results in the accumulation of acidic substances. It was concluded that the pH value of kombucha for 15 days of observation continued to decrease with the lowest value on the 15th day (3.08). Decreasing the pH value can affect microbial growth, acidity, and taste in kombucha.